2007
DOI: 10.1128/mcb.00186-07
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Stranded-RNA Response Program Important for RNA Interference Efficiency

Abstract: When recognized by the RNA interference (RNAi) pathway, double-stranded RNA (dsRNA) produced in eukaryotic cells results in posttranscriptional gene silencing. In addition, dsRNA can trigger the interferon response as part of the immune response in vertebrates. In this study, we show that dsRNA, but not short interfering RNA (siRNA), induces the expression of qde-2 (an Argonaute gene) and dcl-2 (a Dicer gene), two central components of the RNAi pathway in the filamentous fungus Neurospora crassa. The induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 62 publications
1
79
0
Order By: Relevance
“…RNA Analyses-Total RNA was acquired and quantitative real time PCR experiments were performed as described previously (36,37). For these experiments, the ␤-tubulin gene was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…RNA Analyses-Total RNA was acquired and quantitative real time PCR experiments were performed as described previously (36,37). For these experiments, the ␤-tubulin gene was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated that DNA damage agents, such as histidine, HU, or ethyl methanesulfonate, are able to induce the production of qiRNA and QDE-2 protein expression in Neurospora crassa (12,27). In addition, DNA damage-induced QDE-2 expression is abolished in the mutants that are defective in quelling and qiRNA pathways (12).…”
Section: A Genetic Screen Identified Rtt109 To Be Essential For the Dmentioning
confidence: 97%
“…dsal-1, wild-type (301-6, his-3), qde-1 ko (his-3), qde-2 ko (his-3), and dicer dko (his-3) strains were generated previously (Choudhary et al 2007;Maiti et al 2007). The qde-1 ko Ku80 ko his-3 strain was generated in this study by crossing qde-1 ko and Ku80 ko his-3 strains.…”
Section: Strains Growth Conditions and Constructsmentioning
confidence: 99%